2016
DOI: 10.1051/limn/2016019
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of planctomycetes as a nutritional or supplementary food source forDaphniaspp

Abstract: Daphnia magna is widely used as a standard organism in ecotoxicology assays. It plays a key role in energy transfer in freshwater food webs as a primary consumer, grazing on microalgae, yeast and bacteria. Daphnids are commonly reared in the laboratory using microalgae cultures but alternative or complementary sources are important to reduce the dependency on a single food source. The role played in nature by planctomycetes as a food source for other higher trophic levels is still unknown. In this study, we ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 61 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…D. magna is a selective filter feeder organism that feeds on unicellular algae and various organic detritus. The organism becomes a food source for the next trophic level in the aquatic ecosystems because it is naturally essential for fish larvae (Antunes et al, 2016). However, this food chain also leads to the biomagnification of pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…D. magna is a selective filter feeder organism that feeds on unicellular algae and various organic detritus. The organism becomes a food source for the next trophic level in the aquatic ecosystems because it is naturally essential for fish larvae (Antunes et al, 2016). However, this food chain also leads to the biomagnification of pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…since they are non-selective filters. Previous studies conducted by Antunes et al [33] and Marinho et al [34,35] already showed the potential of Planctomycetes, namely Rhodopirellula rubra, to be a good supplementary food source when used in association with the standard food source (the microalgae Raphidocelis subcapitata), and its capacity to improve Daphnia magna life history parameters and in providing pink coloration. The authors also observed that these effects of R. rubra were more relevant at the exponential growth phase than the stationary growth phase.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 This food regime is already discussed as nutritional scarce for a good performance of Daphnia spp. [1][2][3][4][5] In laboratory experiments is essential to guarantee that Daphnia (standard organism) are in excellent conditions in order to respond only to the stress which are in study. So increase the diversity of food sources and nutritional quality is a concern for researchers to assure that Daphnia are in the greatest food and reproductive conditions life-history.…”
mentioning
confidence: 99%